Pembelajaran Berbasis Permainan Dakon Sebagai Implementasi Literasi Budaya Pada Anak Usia Dini di PAUD Al-Amin Bugih Pamekasan - Fadilah; Alfin Herawati; Intan Maya Febriani; Kafilah Rahmawati; Khoirul Ummati; Rahmatika (Institut Agama Islam Negeri Madura, 2024)
This study explores the use of the traditional game Dakon in early childhood education at PAUD AL-AMIN Bugih Pamekasan to develop cultural competence. The background of the research is based on the importance of cultural education for child development and the Indonesian government's efforts to preserve traditional games. This study employs qualitative methods with a descriptive approach, incorporating observation, documentation, and interviews with teachers and students as research instruments. The results show that Dakon-based learning at PAUD AL-AMIN Bugih Pamekasan is implemented through a structured lesson plan consisting of opening, core, and closing activities. Teachers explain the importance of Dakon as a cultural heritage and teach how to play it gradually. This game has proven effective in enhancing various aspects of child development, including motor skills, cognition, emotions, language, social skills, spirituality, ecology, and moral values. Dakon not only helps children learn about Indonesian culture but also boosts their creativity, social interaction, and collaboration skills. This study concludes that early childhood education focusing on traditional Dakon games is an effective method to provide valuable learning experiences and enrich children's cultural understanding while developing various developmental aspects.